IDENTIFICATION OF COMPOSITION, STRUCTURE, AND BIODIVERSITY OF AGROFORESTRY VEGETATION IN THE COMMUNITY FOREST OF SAENAM VILLAGE, WEST MIOMAFFO DISTRICT, NORTH CENTRAL TIMOR REGENCY - Dhenada Nunuhitu; Wilhelmina Seran; Norman P. L. B Riwu Kaho (Ikatan Dosen Menulis, 2024)
The Community Forest Area of Saenam Village, Miomaffo Barat Subdistrict, North Central Timor Regency, located in East Nusa Tenggara, has been utilized for farming using an agroforestry system implemented for the past 5 years to meet the local community's economic needs. This research aims to assess the effectiveness of agroforestry based on the composition, structure, and patterns applied. The study was conducted in Saenam Village, Miomaffo Barat Subdistrict, North Central Timor Regency, using observational methods and vegetation analysis. The results indicate that the highest Importance Value Index (IVI) occurs at the tree, sapling, and pole levels, dominated by the cassowary tree (a native plant in the region) and by cassava (a seasonal crop cultivated by the community) at the seedling level. The highest horizontal structure is found at the tree level with a diameter <10 cm, which is vegetation developed by the community. Vertical structure is dominated by stratum C (4-20m), a combination of natural and cultivated vegetation. The agroforestry pattern applied in the area is Random Mixture, where farmers utilize empty spaces to grow various types of plants.